Zarządzanie (współzarządzanie) sieciowe i zarządzanie sieciami w wymiarze sprawiedliwości – wyzwania - Przemysław Banasik; Sylwia Morawska (Studia i Materiały)
The goal of this paper is the attempt to answer the question whether there is space and reason to implement governance network and networks governance in the justice system and in which area: main or support? In the justice system there is a high potential to use the mechanisms of governance network and networks governance. In the extended area of the justice system inter – organizational cooperation may take up different relations and interactions. The inter – organizational cooperation is possible both in the main and support areas. An excellent tool aimed at the exchange of information and knowledge sharing are communities of practice. They reflect the paradigm of governance network and networks governance in the justice system. The communities of practice intensify the flow of knowledge between and among organizations. In the main area the communities of practice may consist of judges. Their role will be the unification of the legal views in similar cases. This may contribute to the trust to the justice system. In the support area creating the inter – organizational networks will endorse the transfer of good management and organizational practices.